2011
DOI: 10.1093/mp/ssq045
|View full text |Cite
|
Sign up to set email alerts
|

The Simultaneous Repression of CCR and CAD, Two Enzymes of the Lignin Biosynthetic Pathway, Results in Sterility and Dwarfism in Arabidopsis thaliana

Abstract: Cinnamoyl CoA reductase (CCR) and cinnamyl alcohol dehydrogenase (CAD) catalyze the last steps of monolignol biosynthesis. In Arabidopsis, one CCR gene (CCR1, At1g15950) and two CAD genes (CAD C At3g19450 and CAD D At4g34230) are involved in this pathway. A triple cad c cad d ccr1 mutant, named ccc, was obtained. This mutant displays a severe dwarf phenotype and male sterility. The lignin content in ccc mature stems is reduced to 50% of the wild-type level. In addition, stem lignin structure is severely affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
144
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 190 publications
(161 citation statements)
references
References 43 publications
11
144
0
3
Order By: Relevance
“…Given that the NST1 and NST2 genes are responsible for induction of secondary thickening biosynthesis genes and appear to be downstream and regulated by MYB26, we tried to complement the myb26 mutation by overexpression of NST1 and NST2 using the CaMV35S promoter. Secondary thickening in anthers was observed using a combined stain of ethidium bromide, which indicates lignified cells (red fluorescence) and acridine orange, which stains lignified walls with a drop in fluorescence for nonlignified walls (green fluorescence; Stockert et al, 1984;Yang et al, 2007;Thévenin et al, 2011). As previously reported, we observed that the myb26 mutant failed to develop endothecium thickening (Fig.…”
Section: Overexpression Of Nst1 and Nst2 Cannot Complement The Myb26 supporting
confidence: 81%
See 1 more Smart Citation
“…Given that the NST1 and NST2 genes are responsible for induction of secondary thickening biosynthesis genes and appear to be downstream and regulated by MYB26, we tried to complement the myb26 mutation by overexpression of NST1 and NST2 using the CaMV35S promoter. Secondary thickening in anthers was observed using a combined stain of ethidium bromide, which indicates lignified cells (red fluorescence) and acridine orange, which stains lignified walls with a drop in fluorescence for nonlignified walls (green fluorescence; Stockert et al, 1984;Yang et al, 2007;Thévenin et al, 2011). As previously reported, we observed that the myb26 mutant failed to develop endothecium thickening (Fig.…”
Section: Overexpression Of Nst1 and Nst2 Cannot Complement The Myb26 supporting
confidence: 81%
“…The composition of the thickening appears to be critical for dehiscence, since the triple ccc mutant, which is defective for cinnamoyl CoA reductase1, cinnamyl alcohol dehydrogenase c and cinnamyl alcohol dehydrogenase d, has hypolignified stems and accumulates higher amounts of flavonol glycosides, sinapoyl malate. and feruloyl malate, has abnormal endothecium thickening, and is male sterile (Thévenin et al, 2011).…”
mentioning
confidence: 99%
“…These plants presented growth reduction, over-accumulation of anthocyanins and sterility. These phenotypic traits are similar to the ones described in other heavily C3H-repressed [19,21,23] or lignin-down regulated plants [72,73]. 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 …”
supporting
confidence: 78%
“…This process is very challenging because of the high redundancy within the enzyme families involved (21). However, once a sufficient number of biosynthetic mutants were combined, we expectedly observed pleiotropic germination and growth defects.…”
Section: Resultsmentioning
confidence: 97%